An urban geography of the Roman world, 100 BC to AD 300 - Hanson, J. W. 1986- (Archaeopress Roman archaeology, 2016)
This work provides a new account of the urbanism of the Roman world between 100 BC and AD 300. To do so, it draws on a combination of textual sources and archaeological material to provide a new catalogue of cities, calculates new estimates of their areas and uses a range of population densities to estimate their populations.